The Image of the Urban People: Visual Analysis of the Spatialised Demos of Left-Wing Populism in Madrid - García, Óscar; Cossarini, Paolo (Javnost-The Public, 2023)
This paper focuses on the visual representation of “the urban people” by the Spanish left-wing populist party Unidas Podemos (UP) during the campaign for regional elections in Madrid in 2021. The political environment was characterised by increasing polarisation and the hyper-leadership of two candidates, right-wing Isabel Díaz Ayuso and UP’s national leader Pablo Iglesias. In this context, UP employed a diverse range of images and audio-visual material with a specific focus on the urban dimension. This paper explores how the populist logic and societal split—the people vs. the elite—deployed by UP are visually represented and connected with the urban space. Drawing on the central role of images in politics, this paper contributes to the emerging scholarship on the visual and spatial dimensions of populism by (a) exploring the connections between populist imaginary, space, and the visual; (b) advancing an empirical analysis of the image of “the people” in a left-wing political party; and (c) connecting the imaginary of populism to its geo-graphical dimension, stressing both the urban and class divide.